Impact of Concrete Containing Shredded Latex Gloves and Silicone Catheter on the Fresh and Mechanical Properties at Room and Elevated Temperatures - Al Biajawi, Mohammad I.; Izwan, Johari; Rahimah, Embong; Khairunisa, Muthusamy; Joseph Udi, Ufuoma (AIP Publishing, 2023)
In recent years, the number of wastes created by factories, hospitals, building sites, and similar facilities has steadily increased from year to year. The disposal of latex glove and silicone catheter wastes usually is one of the issues of global concern. Furthermore, production of concrete using wastes or abandoned materials as a partial substitution for coarse aggregates is an efficient waste management technique. This strategy can significantly minimize the number of wastes to be disposed of in the landfills and positively influence the properties of concrete. The purpose of this research was to determine the effect of utilizing latex gloves and silicone catheter wastes to substitute a portion of the coarse aggregate in the concrete mixture. Moreover, different percentages (2.5, 5, 7.5, and 10%) of latex gloves and waste were used to replace aggregate in the concrete composite. The evaluation of the properties of fabricated specimens in different temperatures such as (Room Temperature, 400°C) has been conducted, including mechanical and fresh properties. The results showed that the incorporation of different percentages of latex gloves significantly reduced the compressive strength of concrete 86% and 59% at a replacement level of 10% for latex gloves and silicone catheter, respectively. Besides, the addition of latex gloves and silicone catheter waste under elevated temperatures has also decreased the density of concrete to up to 34% and 29% for latex gloves and silicone catheter concrete, respectively. This paper aims to improve environmental awareness by raising the level of knowledge on the generated waste and the importance of recycling such wastes.